A Neurobioethical Perspective on Informed Consent - Lavazza, Andrea (Studia Bioethica, 2019)
The grounding questions are: who is competent? And who is sufficiently competent to be endowed with legal autonomy? My answer: competency can collapse into autonomy if the latter is appropriately defined and it comes in degrees. My definition of autonomy: autonomy amounts to a specific set of neuropsychological capabilities, which can be amenable to objective assessment and quantification. My idea of coming in degrees: autonomy is not an all-or-nothing concept, but in each individual,l it can span from a minimum to a maximum and it is a matter of conventions to set the minimum level of autonomy to give one’s consent in each situations. Neuroscience can’t say when an individual is autonomous because its data underdetermine the understanding and behavioral capacities an individual can display. There is not a direct correspondence between brain functioning and neuropsychological abilities. It is a scientifically informed decision on the degree of autonomy requested which sets the patient’s or participant’s capacity of consent.